Chaperone-dependent stabilization and degradation of p53 mutants - Muller, P; Hrstka, R; Coomber, D; Lane, D P; Vojtesek, B (Oncogene, 2008)
p53 missense mutant proteins commonly show increased stability compared to wild-type p53, which is thought to depend largely on the inability of mutant p53 to induce the ubiquitin ligase MDM2. However, recent work using mouse models has shown that the accumulation of mutant p53 occurs only in tumour cells, indicating that stabilization requires additional factors. To clarify the stabilization of p53 mutants in tumours, we analysed factors that affect their folding and degradation. Although all missense mutants that we studied are more stable than wild-type p53, the levels correlate with individual structural characteristics, which may be reflected in different gain-of-function properties. In the absence of Hsp90 activity, the less stable unfolded p53 mutants preferentially associate in a complex with Hsp70 and CHIP (carboxy terminus of Hsp70-interacting protein), and we show that CHIP is responsible for ubiquitination and degradation of these mutants. The demonstration of a complex interplay between Hsp90, Hsp70 and CHIP that regulate the stability of different p53 mutant proteins improves our understanding of the pro-tumorigenic effects of increased Hsp90 activity during multi-stage carcinogenesis. Understanding the roles of Hsp90, Hsp70 and CHIP in cancers may also provide an important avenue through which to target p53 to enhance treatment of human cancers.
Keywords: mutace; Animals; Tumor Suppressor Protein p53; Enzyme-Linked Immunosorbent Assay; Benzoquinones; Immunoprecipitation; ubikvitinace; protoonkogenní proteiny c-mdm2; Mice, Knockout; Fibroblasts; myši knockoutované; proteiny tepelného šoku HSC70; Neoplasms; nádory; HSP90 Heat-Shock Proteins; lidé; imunoprecipitace; Mice; benzochinony; Mutation; fibroblasty; kultivované buňky; myši; Immunoblotting; Lactams, Macrocyclic; Proto-Oncogene Proteins c-mdm2; Cells, Cultured; Protein Conformation; ELISA; proteiny tepelného šoku HSP90; ubikvitinligasy; makrocyklické laktamy; nádorový supresorový protein p53; HSC70 Heat-Shock Proteins; Ubiquitination; konformace proteinů; imunoblotting; zvířata; Ubiquitin-Protein Ligases; Humans